P.104: 2‐Face Viewable Display Using Dye‐Doped Liquid Crystal. Issue 1 (1st July 2013) - Chen, Chao Ping; Li, Hongjing; He, Zhenghong; Li, Xiao; Xiong, Yuan; Hu, Wei; Su, Yikai; Jhun, Chul Gyu
Abstract: We present a liquid crystal display that allows two faces of the display viewed at opposite directions to show different image/video content simultaneously. This device is characterized by a dye‐doped liquid crystal, which can eliminate the need for polarizers and offer a very low crosstalk between two separated viewing angles.